2001
DOI: 10.1002/jnr.10010.abs
|View full text |Cite
|
Sign up to set email alerts
|

Circadian profile of Per gene mRNA expression in the suprachiasmatic nucleus, paraventricular nucleus, and pineal body of aged rats

Abstract: Aging alters circadian components such as the free-running period, the day-to-night activity ratio and photic entrainment in behavioral rhythms, and 2-deoxyglucose uptakes and neuronal firing in the suprachiasmatic nucleus (SCN). A core clock mechanism in the mouse SCN appears to involve a transcriptional feedback loop in which Period (Per) and Cryptochrome (Cry) genes play a role in negative feedback. The circadian rhythm systems include photic entrainment, clock oscillation, and outputs of clock information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
77
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 39 publications
13
77
0
Order By: Relevance
“…As clock gene oscillation in the SCN was normal in phase II db/db mice, attenuation and arrhythmicity of the locomotor activity and clock gene mRNA rhythm in the liver did not result from a diminishing of the core SCN oscillator but rather from abnormalities stemming from the output mechanism mediating locomotor activity and peripheral clock resetting. Similar results were reported using old animals, in which clock gene expression in the SCN was maintained but locomotor activity was severely diminished [31]. Thus, obesity may be responsible for the reduction of locomotor activity, and hyperphagia may be responsible for the arrhythmicity of locomotor activity in db/db mice.…”
Section: Discussionsupporting
confidence: 84%
“…As clock gene oscillation in the SCN was normal in phase II db/db mice, attenuation and arrhythmicity of the locomotor activity and clock gene mRNA rhythm in the liver did not result from a diminishing of the core SCN oscillator but rather from abnormalities stemming from the output mechanism mediating locomotor activity and peripheral clock resetting. Similar results were reported using old animals, in which clock gene expression in the SCN was maintained but locomotor activity was severely diminished [31]. Thus, obesity may be responsible for the reduction of locomotor activity, and hyperphagia may be responsible for the arrhythmicity of locomotor activity in db/db mice.…”
Section: Discussionsupporting
confidence: 84%
“…Three recent studies have begun to address whether there are changes in molecular rhythm generation in aged animals. In all three studies Period 1 (Per1) and/or Period 2 (Per2) gene expression rhythms were unaffected in the aged SCN [3,19,37]. However, Kolker and colleagues [19] reported that both Bmal1 and Clock expression in the SCN was reduced in aged hamsters.…”
Section: Introductionmentioning
confidence: 92%
“…However, Kolker and colleagues [19] reported that both Bmal1 and Clock expression in the SCN was reduced in aged hamsters. Furthermore induction of Per1 in the SCN by a light pulse was also diminished in aged hamsters [19] and rats [3]. Yamazaki et al [37] investigated rhythmicity in areas outside the SCN in rats using Per1-luciferase reporter gene technology.…”
Section: Introductionmentioning
confidence: 99%
“…In aged animals, Per1 expression following an entraining light stimulus is markedly reduced with a significantly longer delay to resynchronization (Davidson et al, 2008;Kolker et al, 2003). In young animals, disruption of the Period genes leads to aging-like declines in sensitivity to light (Asai et al, 2001;Weinert et al, 2001). These findings suggest that temporal disorganization with advancing age may result, in part, from reductions in the sensitivity of the SCN to retinal stimulation.…”
Section: A Aged-related Changes In Circadian Entrainmentmentioning
confidence: 99%